Dinamika Lembaga Dan Aset Lembaga Perbankan Syariah Di Indonesia (Total Lembaga Dan Aset 2019 – Mei 2023) - Nada, Nabilatun (ITB AAS INDONESIA Surakarta, 2024)
This research utilizes a literature review method to investigate the dynamics of Islamic banking institutions and their assets in Indonesia from 2019 to May 2023. The 2022 Islamic Financial Development Report of Indonesia reveals a significant growth of 15.87% in the assets of the Islamic financial industry. The Financial Services Authority (OJK) emphasizes the resilience of the Islamic economic and financial sector, including Islamic banking, in facing the challenges of the COVID-19 pandemic. In 2022, the assets of the Islamic financial industry reached IDR 2,375.84 trillion, with growth primarily occurring in the Islamic capital market (15.51%) and Islamic Non-Bank Financial Institutions (20.88%). Indonesia remains a key player in the Islamic Finance Development Indicator 2022. This research describes the development of Islamic banking institutions from 2019 to May 2023, highlighting fluctuations in the number of branches and Islamic banks. Consolidation, Islamic financial literacy, and digital technology are key factors shaping the dynamics of this sector. Despite a decrease in the number of Islamic banks, total assets increased from IDR 624.564 trillion in December 2019 to IDR 785.646 trillion in May 2023. These factors support the growth and resilience of the Islamic banking sector in Indonesia.